Exploring Connections Between Self-Compassion, Mindfulness, and Social Anxiety - Makadi, Elisa (Université d'Ottawa / University of Ottawa, 2018)
Social anxiety disorder (SAD) is one of the most common anxiety disorders, with lifetime prevalence rates of 3 to 13% (Statistics Canada, 2015). SAD is characterized by excessive fear of being negatively judged or scrutinized by others in social or performance situations (Cox, Fleet, & Stein, 2004). Previous research has demonstrated a relationship between SAD and self-compassion, and SAD and mindfulness. People with SAD show lower levels of self-compassion compared to healthy controls (Werner et al., 2012), and some research (Neff and Germer, 2013) has indicated that self-compassion can be taught as a skill to enhance levels of self-compassion and overall well-being. As well, mindfulness is a related concept that has been linked to SAD; those with SAD tend to see improvement to their symptoms with mindfulness-based interventions (e.g., Koszycki et al., 2016). Self-compassion and mindfulness are related but distinct constructs that are thought to influence a variety of mental health outcomes. However, few studies have evaluated these constructs concurrently in the context of mental health. The current study examined associations between trait mindfulness, self-compassion and clinical variables in 136 patients with at least moderately severe social anxiety disorder (SAD). Bivariate correlations revealed that higher ratings of self-compassion and facets of mindfulness were associated with less severe social anxiety and depressive symptoms and better functioning and self-esteem. Self-compassion emerged as the strongest predictor of SAD outcomes in regression models. Mediation analysis found that the mindfulness facet Describe served as an indirect mediator in the relationship between self-compassion and severity of clinician-rated social anxiety symptoms. Self-compassion emerged as a mediator between each facet of mindfulness and severity of self- and clinician-rated social anxiety symptoms. Overall, findings from this preliminary cross-sectional study suggest that self-compassion may be a robust indicator of SAD outcomes, and that the ability to label one’s experience may partially explain the self-compassion–SAD symptom relationship. Implications for further SAD research are discussed.
Keywords: Self-compassion; Mindfulness; Anxiety